Analisis Antrian Pada Stasiun Bahan Bakar Umum (SPBU) 2536307 Sungai Bahar Unit V - Manurung, Yessy Hans Aprilia; Manik, Patricia Roma Some; Manurung, Dwi Putri; Situngkir, Elga Yulianti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
As the number of vehicles in Indonesia increases, the need for fuel also increases, creating significant challenges at rural gas stations such as Sungai Bahar Unit V. This research aims to analyze the queuing system at SPBU 2536307, with a focus on the Pertamax line which only has one server. Research data was collected through observations for seven days, recording customer arrivals from 07.00 to 17.00. A quantitative approach using queuing theory, especially the M/M/c model, is used to analyze arrival data, service time, queue length, and service system efficiency. The research results show that the average hourly customer arrival rate ranges from 15.5 to 25.1 vehicles, while the average service time is 2.3 minutes per customer. Queuing system performance analysis reveals the probability of no customers (P₀), the average number of customers in the system (Lₛ), the average time in the system (Wₛ), the number of customers in the queue (Lq), and the average waiting time (Wq ). In peak periods such as 07.00–08.00, the queue reaches an average of 22.73 customers with a waiting time of 0.87 hours. These results indicate that service efficiency can be increased by increasing the number of servers or optimizing service time. The implications of this research offer strategic recommendations for gas station managers to reduce queue lengths and increase customer satisfaction. In addition, this study provides a new perspective on queuing systems in rural areas, which have different characteristics and challenges compared to urban areas.